(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A composite superabsorbent material was synthesized based on silk sericin, acrylic acid and acrylamide by using N, N-methylenebisacrylamide (MBA) as the crosslinker and ammonium persulfate (APS) as the initiator reagent. The water absorbency and water retaining properties of the composite under different preparation conditions were investigated. The absorbency of silk sericin / acrylic acid / acrylamide (SS/AA/AM) superabsorbent polymer polymer in deionized water, tap water and 0.9% NaCl solution were 285337 g/g, 191220 g/g, 3643g/g, respectively. SS/AA/AM material has excellent re-absorbent abilities and can be reused. The product showed different water absorbency in aqueous chloride salt solutions with the order of Na^+ > Ca^2+ > Mg^2+ > Al^3+. FTIR spectra results indicated that silk sericin was successfully grafted with acrylic acid and acrylamide molecules. The study on the absorbent material based on sericin is useful for further research on biodegradable superabsorbent polymer.